The Using of Visual Auditory Read Kinesthetic to Improve Students Reading Ability - Dinar Vincy Yunitaka Bahrudin (The Ellite of Unira, 2018)
Reading is a very important skill to be mastered by every students. Reading is a complex ability. The readers not only look at the symbols written alone, but trying to understand the meaning of the written symbols itself. A good teacher need some method to make students easy in understand the message or the content of a text. Visual Auditory Read Kinesthetic (VARK) model is a new alternative method that is modified by utilizing the modalities held by students. The possess of VARK including visual, hearing, and kinesthetic styles. By applying this model, at the end of the learning process, students are rewarded for their work where the teacher and the entire class applaud. Teachers can also say "Good job" or “Exellent” to improve students' mental and motivate other students to learn, and to create meaningful learning process.            The method used in this study was classroom action research (CAR). The classroom action research design applied in this study was a collaborative classroom action research. It means that the researcher collaborated with English teacher of SMK Kesehatan Bina Husada Pamekasan. This study was conducted by using the procedure of the action research: planning, acting, observing and reflecting. This was carried out in two cycle. The data were gathered in this study trough interview, field note, questioner and test.            The result of the study showed that there was improvement of student reading ability. Most of the students gained good scores at the end of cycle. The Standard Minimum Achievement is 80. The student’s mean score in preleminary study is 62.29. and the class percentage is 23,33%. The mean score in the first cycle is 65.00. and the class percentage is 50,00%.  The mean score in the second cycle is 86.04.and the class percentage is 83,33%. In addition, there was a positive response from the English teacher about implementing the action. In conclusion VARK method can improve students reading ability.